Worse than a physician, Shakespeare and early modern medical practice - Pettigrew, Todd Howard James (University of Waterloo, 1998)
In the sixteenth and seventeenth century, England saw a rising effort on the part of university-trained medical men to create a distinct hierarchy in medical practice. This hierarchy placed medical doctors, particularly the physicians of the Royal College in London, at the top, other licensed practitioners below them, and left a large number of the remaining practitioners unable to practise at all without risking fine and imprisonment. Still, the College's legal power was limited, and to further enforce the emerging medical hierarchy, to solidify its place as a controlling profession, physicians used rhetorical attack to discredit unlicensed healers and to reinforce their own power over practitioners of all kinds. Despite legal measures and printed words, however, traditional healers continued to practice their trade, and many continued to support them. Moreover, authorized practitioners such as apothecaries and surgeons continued to practise in ways that were supposed to be forbidden to them, all the while insisting that their own work deserved more recognition and that their own organizations deserved more power. It is amid this social controversy that Shakespeare creates a variety of medical practitioners in his plays. Medical discourse in his own time created and sustained a variety of available narratives about medical practice, and Shakespeare responds to these narratives in a variety of ways. In some cases, he tells a story that runs directly against the position of the College, England's main medical authority. In other cases, he seems to take a wholly conventional stance. How can such a contradiction be explained? The study finds answers by placing Shakespeare's medical characters in context. The first chapter explores the way in which scholars have conceptualized the connection between Shakespeare and early modern medicine. It divides the criticism into two main traditions: those studies that explore early modern medical belief as displayed in the plays, and those that provide ahistorical overviews of medical practitioners in the plays of Shakespeare and his contemporaries. I argue that the two schools of thought can be usefully fused to provide an account of Shakespeare's practitioners that is historical in its approach. The second chapter examines Helena, the female empiric in All's Well that Ends Well and argues that the play adapts well-known narratives about female medical practice to develop the healing plot. I further suggest that the king's initial rejection of Helena is not merely a matter of medical propriety or straightforward patriarchal oppression, but rather an instance of the complex interweaving of gender and class that was part of early modern practice. The chapter continues the study of female medical practice in Shakespeare by contrasting Helena with Paulina in The Winter's Tale. Paulina, as a member of the nobility, would have been largely shielded from conventional attacks on female healers. She uses this privilege - or rather the fact that these privileges were well-known - to gain a rhetorical advantage in her efforts to save Hermione and restore the kingdom to health. The third chapter considers those practitioners who did not have the status of physicians, but made some claim to legitimate practice. Imposters, men who derived a feigned authority by claiming to be physicians, were widely denounced. The thesis suggests that Caius in The Merry Wives of Windsor is such an imposter - a supposition that would explain his perplexing name. The chapter further considers the role of apothecaries in early modern medicine and traces anxieties over poisoning through to the apothecary in Romeo and Juliet. The chapter also includes a consideration of surgeons in Shakespeare; it asks why there are none. The conspicuous absence, I argue, can best be explained by the difficulty an early modern audience member would have had in distinguishing the social roles played by surgeons and physicians. Surgeons, though different in many ways from physicians, were nevertheless rhetorically indistinct in their identity and so were difficult to use on stage. The chapter also notes how the apparent criticism of the apothecary in Romeo and Juliet is ideologically at odds with the support of the empiric in All's Well. The former provides an implied critique of the "congregated college" while the latter supports its very position. I suggest that this seeming contradiction is best explained by suggesting that Shakespeare creates medical plots and characters with the aim of furthering the dramatic needs of the play, and that the ideological effects, though significant, are, nevertheless, a side-effect, a byproduct of the play's original intent. The next two chapters explore the implications of this ad hoc progression of ideology. Friar Francis (Much Ado About Nothing) and Friar Lawrence (Romeo and Juliet) are the focus of the first part of Chapter 4 which looks at the relationship between medical practice and the use of the supernatural. Along the same lines, I consider the magical healing of Prospero (The Tempest) and Cerimon (Pericles). Chapter 5 considers the physicians in Macbeth and King Lear and outlines the difficult position of the royal physician who must attend to a patient in crisis. Here, I argue that the shadow of the executed Doctor Roderigo Lopez still loomed over the court physician in the early seventeenth century. For the early modern audience, Lopez represented the danger one faced in ceding control of his or her body to another; for the physician, Lopez was reminder of the danger in being caught up in political plotting. The battles fought over medical practice in Shakespeare's England were essentially a matter of credit, by which Elizabethans meant credibility or trustworthiness. Through rhetoric, practitioners attempted to raise their credit, and consequently their social power. It is amidst this struggle that Shakespeare creates his medical characters, and it is to this struggle that Shakespeare's medical characters speak.
Keywords: Harvested from Collections Canada